Measurement of nanometer-thick lubricating films using ellipsometric microscopy. (June 2018) - Fukuzawa, Kenji; Sasao, Yusuke; Namba, Katsuya; Yamashita, Chihiro; Itoh, Shintaro; Zhang, Hedong
Abstract: A method based on vertical-objective-based ellipsometric microscopy (VEM) is presented for measuring lubricant film thickness in nanometer sliding gaps. It provides an image of nanometer-thick lubricating films in real time at high lateral and thickness resolutions without any special layers. The ellipsometric image is directly converted into the film image by using a piezo-stage displacement method combined with a rotating compensator ellipsometry method. The accuracy of thickness measurement is about 1 nm. The VEM-based method revealed that nanometric deformation of the sliding surfaces arises in nanometric gaps even if the load is low, which significantly affects the lubrication properties in small gaps. This method is useful for clarifying the lubrication phenomena in nanometric sliding gaps. Highlights: A new method for measuring lubricant film thickness in nm-sliding gaps is proposed. The measurement method based on ellipsometric microscopy was first demonstrated. The method does not require coating of sliding surfaces with special layers. The method provided real-time measurement with a thickness accuracy of about 1 nm. The method revealed nanometric deformation of sliding surfaces in nm-sliding gaps.